Occult Hepatitis-B Infection in Volunteer Blood Donors in Different Hospitals of Peshawar, Khyber Pakhtunkhwa - Ahmad, Bashir (International Journal of Pathology, 2020)
Background: Although screening tests are performed in hospitals of Khyber Pakhtunkhwa, but still some tests are being ignored due to that potential infection is being transmitted. Objective: This study was designed to find out potential HBV infection transmitted through blood transfusion. Methodology: In this regard, 200 blood samples, negative for both (anti-HCV and HBsAg) were screened for HB core infection through ELISA technique after screening of routine procedures in the blood banks. Anti-HB core Positive samples were then processed for active HBV infection using Real time PCR. Results: Out of 200 samples, 17 (8.5%) were positive for anti-HB core and about 4 (23.5%) of the subjects had active HBV infection. Conclusion: It was concluded that HB core infection was present in apparently healthy individuals. Hence this study suggests that anti-HB core test should also be included in routine screening procedures in different hospitals of KPK.